LARVICULTURA DE PIAU CORRÓ (Leporinus lacustris) EM DIFERENTES MANEJOS ALIMENTARES - ORUÊ, Andrey Makálister Souza; MACHADO, João victor Bezerra; ROMERO, João Pedro Alves; SANTOS, Jussara Garrido dos; ACUNHA, Rubia Mara Gomes; COSTA, Deliane Cristina (ANAIS DO ENIC, 2023)
-